2017
DOI: 10.1007/s00268-017-4172-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Electronic Surgical Outcomes Database at Mbarara Regional Referral Hospital, Uganda

Abstract: SQUAD is an electronic surgical database that has been implemented and sustained in a low-resource setting. For the 20 variables evaluated, the data within SQUAD are highly complete and accurate. This database may serve as a model for the development of additional surgical databases in low-resource environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…We found that almost all the studies focused on either safety32–35 40–42 44–46 48 51–53 59–81 and/or effectiveness of care, with a lack of focus on other domains of quality. The prioritisation on safety was not surprising given the well-recognised magnitude of the patient safety problem21 and the resultant global movement to improve patient safety.…”
Section: Discussionmentioning
confidence: 98%
“…We found that almost all the studies focused on either safety32–35 40–42 44–46 48 51–53 59–81 and/or effectiveness of care, with a lack of focus on other domains of quality. The prioritisation on safety was not surprising given the well-recognised magnitude of the patient safety problem21 and the resultant global movement to improve patient safety.…”
Section: Discussionmentioning
confidence: 98%
“…A strength of the study was that the chart review was exhaustive with minimal missing data, which overcomes a common problem for tracking outcomes in resource-limited settings. 35 The intervention was performed as a quality improvement initiative, without any intentional changes in documentation or detection of complications. We do not know if the impact will be sustained over a more extended time period, and further analysis of future patients is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Chart selection: we obtained the medical records numbers of all women admitted to MRRH maternity ward from a surgical services quality assessment registry created to track surgical outcomes at MRRH. All maternity ward hospitalizations were captured using this registry between 2013 and 2014 and coded by admission diagnosis [ 15 , 16 ]. The registry included details on surgical procedures and hospital outcomes but did not include clinical documentation such as vital signs.…”
Section: Methodsmentioning
confidence: 99%